ChemInform Abstract: The Development of a One Pot, Regiocontrolled, Three‐Component Reaction for the Synthesis of Thieno[2, 3‐c]pyrroles. Issue 36 (15th August 2013) - Hong, Cynthia M.; Statsyuk, Alexander V.
Abstract The reaction is conducted under environmentally benign conditions.